SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN TENAGA AHLI PADA DINAS KOMINFO KABUPATEN DELI SERDANG MENERAPKAN METODE VIKOR - Harahap, Arahman; Mesran, Mesran; Ramadhan, Saidi; Waruwu, Fince Tinus (STMIK Budi Darma, 2018)
The Ministry of Communication and Informatics carries out communication and informatics services to the public as well as supervising and regulating licensing in the field of Communication and Information to government and community institutions. For this reason, the Communication and Information Agency of Deli Serdang Regency recruits experts with predetermined criteria. An expert is someone who is considered a trusted source of certain techniques and expertise in assessing and deciding things correctly, well, and reliably in accordance with a particular field. a decision support system in selecting experts using the method. Decision support systems can solve unstructured problems. In general, a decision support system is built in order to guide the steps in deciding a decision using the SPK method. One of the SPK methods, namely VIKOR, is a method that focuses more on ranking between alternatives and interconnected criteria.Keywords: Decision Support Systems, VIKOR Method, Experts